2010
DOI: 10.1063/1.3309702
|View full text |Cite
|
Sign up to set email alerts
|

A nondestructive analysis of the B diffusion in Ta–CoFeB–MgO–CoFeB–Ta magnetic tunnel junctions by hard x-ray photoemission

Abstract: This work reports on hard x-ray photoelectron spectroscopy (HAXPES) of CoFeB based tunnel junctions. Aim is to explain the role of the boron diffusion for the observed improvement of the tunneling magnetoresistance ratio with increasing annealing temperature. The high bulk sensitivity of HAXPES was used as a nondestructive technique to analyze CoFeB–MgO–CoFeB magnetic tunnel junctions. The investigated samples were processed at different annealing temperatures from 523 to 923 K. Hard x-ray core level spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 9 publications
6
53
0
Order By: Relevance
“…For example, theoretical studies have suggested that the band structure of MgO-B also can provide a route for coherent tunneling of electrons and the diffusion of * Also at Jawaharlal Nehru Centre for Advanced Scientific Research, Bangalore 560064, India; sarma@sscu.iisc.ernet.in boron may even be beneficial for the TMR in the device [26]. Other reports [16,20] claim that B rather migrates away from MgO, into the cap layer of Ta, resulting in TaB favoring high TMR [16,17]. Thus, while great steps have been made toward improving device performances substantially, there are significant gaps in our understanding of these device structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, theoretical studies have suggested that the band structure of MgO-B also can provide a route for coherent tunneling of electrons and the diffusion of * Also at Jawaharlal Nehru Centre for Advanced Scientific Research, Bangalore 560064, India; sarma@sscu.iisc.ernet.in boron may even be beneficial for the TMR in the device [26]. Other reports [16,20] claim that B rather migrates away from MgO, into the cap layer of Ta, resulting in TaB favoring high TMR [16,17]. Thus, while great steps have been made toward improving device performances substantially, there are significant gaps in our understanding of these device structures.…”
Section: Introductionmentioning
confidence: 99%
“…While device fabrication has been empirically refined to meet strict quality demands, the fundamental understanding of the modifications in the TMR structure introduced by various optimization processes, e.g., postannealing [8][9][10][11][12][13][14][15][16], resulting in a different magnitude of the TMR [10,11], is still missing. In particular, the behavior of boron, apparently playing a crucial role for high magnetoresistance, has remained controversial in spite of extensive investigations [12,13,[15][16][17][18][19][20][21][22][23][24]. For example, it has been suggested that B diffusion is integral to the creation of a textured CoFe alloy and consequently, high TMR.…”
Section: Introductionmentioning
confidence: 99%
“…Hard x-ray photoelectron spectroscopy (HAXPES) has therefore enjoyed increasing attention. [1][2][3][4][5] The combination with variable photon polarization with this technique provides a unique tool for the investigation of the electronic and magnetic structures of deeply buried layers and interfaces. 6,7 Magnetic circular dichroism measures the difference of the photoemission intensity for left and right circularly polarized x rays.…”
Section: Introductionmentioning
confidence: 99%
“…For hν > 8 keV, the bulk spectral weight was found to reach more than 95% [3]. Hard X-ray photoelectron spectroscopy (HAXPES) has been found to be a well-adaptable non-destructive technique for the analysis of chemical and electronic states [4,5]. It was recently shown that HAXPES can be combined easily with variable photon polarization when using phase retarders [6].…”
Section: Introductionmentioning
confidence: 99%